New records of Palaeocorystoidea from the Iberian Peninsula and remarks on the taxonomic significance of the posterior margin of Cenomanocarcinus Van Straelen, 1936 and Hasaracancer Jux, 1971 (Decapoda; Brachyura; Cenomanocarcinidae) - Ossó, Àlex (Zootaxa, 2017)
Two species of Cenomanocarcinus (Cenomanocarcinidae) from the late Albian and Turonian of Spain are reported herein, increasing the number of Iberian Cenomanocarcinus species. Likewise, Necrocarcinus woodwardii (Necrocarcinidae) is reported for the first time in the Iberian Peninsula and constitutes the southernmost record for the species. As well, the features of the posterior margin of the cenomanocarcinids Cenomanocarcinus and Hasaracancer, are reviewed and clarified.